Scaling up high-impact interventions: How is it done?. (June 2015) - Smith, Jeffrey Michael; de Graft-Johnson, Joseph; Zyaee, Pashtoon; Ricca, Jim; Fullerton, Judith
Abstract: Building upon the World Health Organization's ExpandNet framework, 12 key principles of scale-up have emerged from the implementation of maternal and newborn health interventions. These principles are illustrated by three case studies of scale up of high-impact interventions: the Helping Babies Breathe initiative; pre-service midwifery education in Afghanistan; and advanced distribution of misoprostol for self-administration at home births to prevent postpartum hemorrhage. Program planners who seek to scale a maternal and/or newborn health intervention must ensure that: the necessary evidence and mechanisms for local ownership for the intervention are well-established; the intervention is as simple and cost-effective as possible; and the implementers and beneficiaries of the intervention are working in tandem to build institutional capacity at all levels and in consideration of all perspectives.